The role of income and demographic effects in determining poverty transitions for individuals : evidence from the KwaZulu-Natal Province, 1993 to 2004 - Hove, Fidelis (School of Economics, 2014)
Includes abstract. Includes bibliographical references (leaves. 42-44).